Three Years of Colonoscopy Experience in a Tertiary Hospital in Maldives - Khadka, Mohan (Journal of Nobel Medical College, 2022)
Background: Colonoscopy is the procedure of choice in investigations of suspected pathologies related to colon and terminal ileum and the standard practice for screening colonic polyps and cancer, especially in the elderly. Adequate bowel preparation is important for the efficacy of the procedure. As there is a lack of published data on colonoscopy preparation and findings in the Maldives, this study was conducted to share the single-center experience. Materials and Methods: This was a retrospective observational preliminary study carried out in the endoscopy center at ADK hospital, Maldives from April 2017 to March 2020. All patients were evaluated as per pre-designed Pro-forma. The procedure was performed after a pre-anesthetic check-up with intravenous sedation after bowel preparation as protocol. Findings were noted and Biopsies were taken as per need and sent for histopathologic examination. Results: Out of 129 patients who underwent lower gastrointestinal endoscopy, only 98 were included for the study analysis. Among them, 44% of patients were male and 56% were female. Young adults were more involved in the procedure. Bowel preparation was poor in the majority (52%). Bleeding per rectum was the most common indication (40%) and hemorrhoids were the most frequent finding (52%). In 86% of patients, colonoscopy was complete up to cecum with the majority of them up to terminal ileum. Conclusion: Per rectal bleeding was the most common indication for colonoscopy and hemorrhoids were the most common findings. Despite poor bowel preparation due to the lack of a standard cleansing regimen, the yield of the procedure was yet satisfactory.